Actividades de risoterapia para fortalecer el desarrollo bio psicosocial de los pacientes del Hospital General Yerovi Mackuart” del cantón Salcedo provincia Cotopaxi parroquia San Miguel en el periodo 2014 -2015 - Quispe Toscano, Ximena Mercedes (2015)
By analyzing applied in the General Hospital "Yerovi Mackuart" the problem that appeared in children / as detected, such as bio-psychosocial development can be observed by their state of emotional and intellectual courage. The research ingwork contains very important aspects in relation to the activities of the risotherapy, as it is a very efficient action to help them recover children / in the General Hospital, it has been proposed to perform the work in order to provide anencourage for this problem with some dynamics of the activities of the risotherapy to benefit the health of infants, this will eliminate these problems in the bio-psychosocial development. In this document the activities of the risotherapy, exposes including a theoretical framework where the importance and activities riso-therapy to help us to bio-psychosocial development as well as the consequences of are described first this issue and finally the activities to do with children.